Prevalence of Child Sexual Abuse in Spain: A Representative Sample Study - Ferragut, Marta (Journal of interpersonal violence, 2022)
The prevalence of child sexual abuse (CSA) is difficult to assess, and rates vary widely across studies due to methodological and sample differences. In Spain, prevalence data from representative samples are lacking. The objective of this study was to determine the prevalence of different CSA experiences in a sample that was representative of the Spanish population in terms of gender, age, and region. The sample comprised 1,071 (539 male and 532 female) Spanish adults (Mage = 45.37; SD = 14.84). Participants completed an anonymous online survey about different types of CSA and were asked whether they had disclosed the experience at the time. Prevalence was analyzed as a function of gender and generation. Results indicated prevalence rates ranging from 2.8% to 18.5%, depending on the type of experience. The most common experience suffered during childhood was being shown pornographic material, while that with the lowest prevalence was being forced to perform a sexual act involving penetration. Prevalence was higher in females than males for eight of the ten experiences considered. Young adults from Generation Z were the most likely to report having suffered three of the CSA experiences, two of them related to technology. Only 27.5% of respondents said that they had told someone about the abuse at the time, mainly their mother (more common among females) or a friend/peer (more frequent among males). The results suggest that CSA is prevalent in Spain, with considerable rates for several types of abusive experience, especially among females and the youngest generation. The implications of the results are discussed. The findings may inform social policy and the development of effective prevention programs.